Management of Acute Respiratory Distress Syndrome Due to Transfusion-Related Acute Lung Injury and Pulmonary Contusion in a Patient with Moderate Head Injury Post-Craniotomy Decompression, Epidural Hematoma, and Posterolateral Rib Fractures 2-6 - Hendro, Rachmad Try; Pison, Osmond Muftilov (Journal of Society Medicine, 2025)
Introduction: Acute Respiratory Distress Syndrome (ARDS) is characterized by acute onset within seven days of an insult, leading to impaired gas exchange, respiratory distress not attributed to cardiac pump dysfunction, and diffuse bilateral opacities on chest X-ray (CXR). ARDS can result from direct lung parenchymal injury, such as pulmonary contusion, or indirect mechanisms, such as transfusion-related acute lung injury (TRALI), which triggers inflammatory mediator release, causing capillary leakage and damage to type I and II pneumocytes. Case Description: A 50-year-old male was admitted to the Intensive Care Unit (ICU) following a craniotomy evacuation. On the second day of ICU care, after receiving four units of packed red cell (PRC) transfusion and subsequent extubation, the patient developed dyspnea, increased respiratory rate, elevated work of breathing, and desaturation. Clinical examination revealed decreased consciousness, tachycardia, tachypnea, and desaturation. Diagnostic imaging showed diffuse bilateral opacities without cardiac abnormalities. The patient was re-intubated and connected to a ventilator using a lung protective strategy. Broad-spectrum antibiotics and adequate tissue perfusion support were administered. The patient showed improvement and was discharged from the ICU. Conclusion: ARDS, whether caused by direct insults like pulmonary contusion or indirect mechanisms like TRALI, requires a lung protective strategy to preserve healthy lung tissue. Early recognition and appropriate ventilatory management are critical for improving outcomes in such cases.